Anatomical Predisposition of the Ankle Joint for Lateral Sprain or Lateral Malleolar Fracture Evaluated by Radiographic Measurements. (January 2015) - Lee, Kyoung Min; Chung, Chin Youb; Sung, Ki Hyuk; Lee, SeungYeol; Kim, Tae Gyun; Choi, Young; Jung, Ki Jin; Kim, Yeon Ho; Koo, Seung Bum; Park, Moon Seok
Background: Injury mechanism and the amount of force are important factors determining whether a fracture or sprain occurs at the time of an ankle inversion injury. However, the anatomical differences between the ankle fracture and sprain have not been investigated sufficiently. This study was performed to investigate whether an anatomical predisposition of the ankle joint results in a lateral malleolar fracture or lateral ankle sprain. Methods: Two groups of consecutive patients, one with lateral malleolar fracture (274 patients, mean age 49.0 years) and the other with lateral ankle sprain (400 patients, mean age 38.4 years), were evaluated. Ankle radiographs were examined for 7 measures: distal tibial articular surface (DTAS) angle, bimalleolar tilt (BT), medial malleolar relative length (MMRL), lateral malleolar relative length (LMRL), medial malleolar slip angle (MMSA), anterior inclination of tibia (AI), and fibular position (FP). After an interobserver reliability test, the radiographic measurements were compared between the 2 groups. Linear regression analysis was performed to correct for age and sex effects between the groups. Results: The fracture group and the sprain group showed significant differences in BT ( P = .001), MMSA ( P < .001), AI ( P = .023), and FP ( P < .001). In multiple regression analysis, after adjusting for age and sex effects, fracture and sprain groups showed a significant difference in BT ( P = .001), MMRL ( P < .001), MMSA ( P < .001), and FP ( P < .001). Conclusions: The lateral malleolar fracture group tended to show more bony constraint than that of the lateral ankle sprain group. Further 3-dimensional assessment of the bony structure and subsequent biomechanical studies are needed to elucidate the mechanism of injury according to the various types of ankle fractures and ankle sprain. Level of Evidence: Level III, retrospective comparative study.